Productive potential of Cedrela odorata L.: estimation through the 3-PG model - Montero-Solís, Flor María; Álvarez-Muñóz, José; López-López, Miguel Ángel (Instituto de Ecología, A.C., 2019)
The productivity of forest systems in the Mexican tropics has been severely constrained by the lack of silvicultural practices that promote their competitiveness. Red cedar wood is an economically important specie in the Mexican tropics, and little is known about yields and how to improve its productivity. The 3-PG model (Physiological Processes Predicting Growth) allows to predict the growth of a stand even in areas where the species has not grown, estimating the productivity of the site. The present study estimated the growth and effect of nutrition on the species through the 3-PG model from the physiological variables of the species and similar one. Foliage biomass mean diameter at breast height, in the fertilized condition increased when fertilization was considered in the stand. The year five was the one that registered the highest volume in the condition with fertilization (FR = 0.6) of 66.9 m3 ha-1 vs without fertilization (FR = 0.3), 51.9 m3 ha-1. In addition, the stem volume (m3 ha-1), trunk biomass (Mg ha-1) and height (cm) also increased with the age of the stand in the fertilization treatment. The 3-PG model is applied for the first time in this species and in Mexico, so it is necessary to continue with ecophysiological studies of the species and aspects of nutrition, to achieve a better prediction of growth and to be a useful tool in decision making of forest management.